Revd Jan Zowczak's Sociopedeutological Research in the Context of Successive Stages of Teachers' Code of Ethics Development - Bogusław Śliwerski (Nicolaus Copernicus University in Toruń, 2011)
The author explores the issues in Revd Jan Zowczak's sociopedeutological research in the context of the 1980s debate regarding teachers' professional ethics and the necessity to elevate the moral condition of the teaching profession through adoption of the teachers' code of ethics.